Poverty and Asset Distribution among Korea's Elderly According to Household Type and Public Pension Beneficiary Status - Heesuk Yun; Hyungjoon Kwon (Korea Development Institute (KDI), 2014)
- Poverty among the elderly is a serious social issue in Korea, an there is a broad consensus that social policy measures are urgently needed. - The average elderly poverty rate among OECD countries is 13.5%. Korea's rate is 45.1%, 3.4 times higher. - The country also faces a suicide rate among the elderly that is nearly four times the average for OECD countries, with poverty widely understood to be an underlying factor. - An effective response to poverty among the elderly requires an accurate determination of which segments of the population are better and worse off. - The higher poverty rate among the elderly does not necessarily imply that the same policies should be applied to all of Korea's elderly. Indeed, not taking consideration of differences within the elderly population could result in the failure to assist those mired deep in poverty. - The result of failing to detect differences in financial means between segments of the elderly population is that resources are more likely to be directed to those living under relatively favorable conditions, while those with greater needs are neglected. - Poverty was found primarily in single elderly households; the poverty rate for those living with working-age household members was not significantly different from that of the overall population. - Poverty was primarily found in households without working-age members in which elderly individuals lived alone or with young people below the working age. The poverty rate for this segment was 70.9%, compared to 18.7% for households where elderly individuals lived with their children or other working-age adults. - For elderly people who lived with working-age adults, a high proportion of family income and assets was found to belong to the latter. This has led to the mistaken perception that such elderly individuals are even worse off than single elderly people, resulting from only taking into account the economic resources that are listed in the names of the elderly individuals. - Among public pension beneficiaries, a high degree of similarity was found in the level and distribution of assets for those receiving special occupation pensions. National pension recipients generally received small payouts, with high levels of inequality in asset distribution. At the lowest level, their situation differed little from that of non-recipients. - In contrast with the social insurance system, which is based on the principle of contribution, public assistance and social services are need-based. Criteria for the latter systems should therefore be crafted to accurately reflect and effectively remedy poverty among the elderly. - To avoid potential negative effects stemming from support obligor provisions in the basic livelihood security system, the economic resources of adult children are not taken into account at all in awarding the basic old-age pension. This has resulted in severe distortions in support priorities since the actual economic resources of the elderly vary depending on the presence or absence of adult children within the household. - This suggests a need to account for the economic resources of adult children who are members of the household as a way of gauging the level of actual economic resources while still avoiding the potential pitfalls of the support obligor standards. - A more effective policy approach for addressing poverty among the elderly prioritizing those with the most urgent need based on accurate assessments of the economic resources of the entire household needs to be taken.
Keywords: 330